2008
DOI: 10.1099/jmm.0.2008/001875-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of invasive and non-invasive Streptococcus pyogenes isolates from Romania

Abstract: In 2002, the Romanian National Reference Laboratory was invited to join the Strep-EURO project to study invasive Streptococcus pyogenes infections. During 2003 and, a total of 33 isolates recovered from invasive disease were received from eight Romanian counties. For comparison, 102 isolates from non-invasive disease, as well as a collection of 12 old invasive strains (isolated between 1967 and 1980) were included. All isolates were characterized by several methods: T and emm typing, presence of the fibronect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
4
8
0
2
Order By: Relevance
“…In the year 2003, the study conducted at our laboratory showed predominance of emm 81 type in North Indian community, which has also been reported from other countries [8,16,18,19,20]. Report of association of emm 81 with invasive disease in Sweden and Romania [17,20] prompted us to look for a virulent potential of the circulating predominant emm 81 isolates from our community.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In the year 2003, the study conducted at our laboratory showed predominance of emm 81 type in North Indian community, which has also been reported from other countries [8,16,18,19,20]. Report of association of emm 81 with invasive disease in Sweden and Romania [17,20] prompted us to look for a virulent potential of the circulating predominant emm 81 isolates from our community.…”
Section: Discussionsupporting
confidence: 74%
“…Report of association of emm 81 with invasive disease in Sweden and Romania [17,20] prompted us to look for a virulent potential of the circulating predominant emm 81 isolates from our community. We focused on adherence and invasion potential of these isolates towards host cell, the process resulting in infection or disease outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genotype emm1.0 and emm12.0 strains were prevalent in invasive and noninvasive diseases (Luca-Harari et al, 2008b). Genetic mutation was the major culprit for the outbreak of S. pyogenes infection.…”
Section: Discussionmentioning
confidence: 99%
“…HaeIII vir typing patterns of Australian GAS isolates produced 4 to 8 fragments ranging from 200 bp to 4 kb, where 1.4 kb, 500 bp, and 275 bp were found common in the isolates tested [9]. vir typing patterns of Romania yielded 2 to 8 fragments ranging from 100 bp to 4.2 kb with a common fragment at 1.2 kb [42]. Reports from north India showed 4 to 6 fragments varying from 300 bp to 5 kb where 300 bp, 550 bp and 1.2 kb were common for the majority of isolates [15].…”
Section: Discussionmentioning
confidence: 99%